2018
DOI: 10.17219/acem/68474
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of thromboprophylaxis in patients hospitalized for pulmonary disorders: A single-center retrospective study

Abstract: Background. Underuse of thromboprophylaxis in hospitalized medical patients is still common worldwide. Little is known about the use of thromboprophylaxis in patients with pulmonary diseases in everyday hospital practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our study reported that prophylactic LMWH is more commonly used among lung cancer inpatients compared with those suffering from a wide range of pulmonary diseases in the same Polish tertiary hospital [ 20 ]. Awareness of the VTE risk, as the most common preventable cause of death in hospitals, has increased in Poland, where several local guidelines have been issued over the last 10 years [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study reported that prophylactic LMWH is more commonly used among lung cancer inpatients compared with those suffering from a wide range of pulmonary diseases in the same Polish tertiary hospital [ 20 ]. Awareness of the VTE risk, as the most common preventable cause of death in hospitals, has increased in Poland, where several local guidelines have been issued over the last 10 years [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used two validated scoring systems to identify patients at high risk for VTE when hospitalized, i.e. the Padua prediction score and Caprini VTE risk assessment [ 3 , 19 , 20 ]. The Padua prediction score, indicating a high risk, was defined as a score of 4 or higher.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective study based on prediction scores found that 65.2% of patients did not receive suitable coagulation prophylaxis (p < 0.001). Hence, it was concluded that coagulation prophylaxis is underused in hospital patients with pulmonary diseases by taking into consideration the scoring system used [46,47]. Severe patients, mechanical ventilation, and medications such as sedatives were the main risk factors that contributed to the high risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 cohort comprises all adult patients hospitalized from April 1, 2014, to December 31, 2014, who were admitted prior to the implementation of the use of the Caprini tool. 17 All archived records of patients were analyzed and scored using the Caprini VTE risk assessment tool, and the final score was compared with archived records of admitted patients who received thromboprophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…16 A frequent overuse and underuse of thromboprophylaxis was observed in our previous study when the decision to administer prophylaxis was at the discretion of the treating physician. 17 To improve thromboprophylaxis, a computerized system based on the Caprini risk assessment was implemented.…”
Section: Introductionmentioning
confidence: 99%